2010
DOI: 10.1371/journal.pone.0010999
|View full text |Cite
|
Sign up to set email alerts
|

Safety Concern between Autologous Fat Graft, Mesenchymal Stem Cell and Osteosarcoma Recurrence

Abstract: BackgroundOsteosarcoma is the most common malignant primary bone tumour in young adult treated by neo adjuvant chemotherapy, surgical tumor removal and adjuvant multidrug chemotherapy. For correction of soft tissue defect consecutive to surgery and/or tumor treatment, autologous fat graft has been proposed in plastic and reconstructive surgery.Principal FindingsWe report here a case of a late local recurrence of osteosarcoma which occurred 13 years after the initial pathology and 18 months after a lipofilling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 107 publications
(76 citation statements)
references
References 54 publications
(63 reference statements)
3
71
0
2
Order By: Relevance
“…Therefore, dialogs between these cells are possible [13]. In 2010, Perrot et al reported a case of a late local recurrence of osteosarcoma occurring more than 10 years after the initial pathology and 18 months after a "lipofilling" procedure [38]. In complement of this observation, the co-injection of purified mesenchymal stem cells promoted the osteosarcoma development in a murine model, then underlying a functional interaction between osteosarcoma cells and mesenchymal stem cells.…”
Section: Cellular Heterogeneity Of the Osteosarcoma Microenvironment:mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, dialogs between these cells are possible [13]. In 2010, Perrot et al reported a case of a late local recurrence of osteosarcoma occurring more than 10 years after the initial pathology and 18 months after a "lipofilling" procedure [38]. In complement of this observation, the co-injection of purified mesenchymal stem cells promoted the osteosarcoma development in a murine model, then underlying a functional interaction between osteosarcoma cells and mesenchymal stem cells.…”
Section: Cellular Heterogeneity Of the Osteosarcoma Microenvironment:mentioning
confidence: 99%
“…Several studies have confirmed that mesenchymal stem cells promote the proliferation of osteosarcoma cells both in vitro and in vivo [38,[46][47][48][49]. Mesenchymal stem cells, the low differentiated precursor of various cell-types including osteoblast [16], in contrast to differentiated osteoblasts appear unable to communicate with osteosarcoma cells through the establishment of functional gap junctions [50].…”
Section: Mesenchymal Stem Cells Control Osteosarcoma Development: Potmentioning
confidence: 99%
“…Previous investigators have shown that MSCs promote both primary and metastatic tumor growth when coinjected in the presence of established primary osteosarcoma or concurrently with osteosarcoma cell lines [3,24,28,29]. This effect of MSCs has been shown with other tumor types as well [4,14,20].…”
Section: Discussionmentioning
confidence: 83%
“…Perrot et al [95] raised concern of osteosarcoma recurrence after autologous fat grafting, reporting a case of late recurrent osteosarcoma 13 years after the use of a lipoilling procedure. Following this they utilised a pre-clinical murine model of osteosarcoma to show that injection of fat grafts and MSCs promoted tumour growth.…”
Section: Mesenchymal Stem Cell Utilization For Biological Reconstructionmentioning
confidence: 99%